EFFECT OF LEVEL OF CONCENTRATE FEEDING LEVEL ON EFFICIENCY OF EATING BEHAVIOUR ON ONGOLE CROSSBRED CATTLE - Dartosukarno, S.; Iskandar, F.; Purnomoadi, A. (Diponegoro University, 2012)
Eight bulls of Ongole Crossbred (OC) cattle with initial body weight (BW) of 297 + 26 kg (CV =8.75%) fed rice straw treated with urine (RU) (ad libitum) were divided into two groups (each fourheads) to determine the effect of concentrate feeding level on efficiency of eating behavior. The cattlewas given concentrate feeding composed of beer cake and rice bran to make 14% crude protein at 1%and at 2% BW for RUC1 and RUC2 group, respectively. Eating behavior was measured for 3x24 hoursand was performed twice at weeks 2 and 6 of the study. Data obtained were analyzed by t-test. Theresults showed that the level of concentrate feeding affected the intake of urinated rice straw (P<0.01)and daily BWGain (P<0.05), but the effect was not found (P>0.05) on DMI, length time for eating(196.5 vs. 221.5 min/d), length time for rumination (351.0 vs. 449.4 min/d), efficiency of eating time(37.21 vs. 37.67 gDM/min) and efficiency rumination time (21.43 vs. 18.50 gDM/min). This researchshowed that concentrate feeding at 2% BW did not alter the efficiency of eating time and ruminationcompared to 1% BW, although able to improve BWG of OC cattle.